Seaweeds as a potential resource in diabetes management: a review - J. S. Vidyashree; Priya P. Shetti; Shridhar C. Ghagane (SpringerOpen, 2024)
Abstract Background Seaweeds are the marine macroalgae predominantly found in the coastal regions. These species have unique chemical profiles which makes them stand different from terrestrial plants. They are found to be rich in secondary metabolites which have potential in treating various unhealthy conditions. Diabetes is a chronic condition where an individual suffers from high or low sugar levels in the blood. Main text This review article aims to review such seaweed species that are potent in treating and managing diabetes. It has become one of the rapidly growing diseases in the world with a high occurrence rate. This paper details the mechanism of glucose regulation in the human body. Seventy percent of the total earth's surface is accomplished by marine ecosystem. It offers home for about 25,000 species. Among them, many possess health benefits hence these are utilized directly as food or in the form of medicine. Conclusion In this article, various such seaweed species which have antidiabetic property has been discussed. Including edible seaweeds in daily diet have numerous healing properties. Inhibition of alpha amylase and alpha glycosidase enzyme has been associated with lowering the postprandial glucose level. This review article attempts in exploring how seaweeds and managing diabetes are interrelated.